The Oxford handbook of strategy. Vol. 1, A strategy overview and competitive strategy - Faulkner, David, 1938-; Campbell, Andrew, 1950 Aug. 3- (Oxford handbooks in business and management., 2006)
This volume presents an analysis of how thinking on strategy has evolved and what the likely developments in the near future are. All the contributors are experts in their area, and bring to the topic an understanding informed by many years' experience of research, teaching, and practice.